Characterization, treatment and outcomes of salivary ductal carcinoma using the National Cancer Database. (August 2017) - Osborn, Virginia; Givi, Babak; Lee, Anna; Sheth, Niki; Roden, Dylan; Schwartz, David; Schreiber, David
Highlights: SDC currently has no well-defined treatment guidelines. 495 cases from 2004 to 2013 are reviewed from the National Cancer Database. Surgery remains the primary treatment modality, as with other salivary tumors. Adjuvant therapy is frequently used although no significant survival benefit was seen. Abstract: Objectives: To analyze clinical, treatment and outcome data for patients with salivary ductal carcinoma in a large population-based sample. Materials and methods: The National Cancer Database was queried to identify patients diagnosed with salivary ductal carcinoma between 2004 and 2013. Kaplan Meier and Cox regression analysis were used to assess overall survival (OS) and identify impact of specific variables on OS. Results: A total of 495 patients were identified. The most common site of tumor origin was the parotid (80%). 130 patients (26.3%) presented with early stage (I-II) disease, 257 patients (51.9%) with locoregionally advanced pathologic stage (III-IVB) disease and 41 patients (8.3%) with metastatic disease. The 5 year OS for these patients was 79.5%, 40.4% and 0% respectively. At presentation, 46.6% had node positive disease. Surgery was performed in 100% of patients with early stage disease, 98.4% with advanced disease and 90.2% with metastatic disease. Radiation therapy, generally postoperative radiation, was given to 58.5% of patients with stage I-II disease, 71.6% with stage III-IVB disease and 53.7% with metastatic disease. Chemotherapy was utilized in 5.4% of patients with stage I-II disease, 35% with stage III-IVB and 70.7% with metastatic disease. On multivariable analysis, there were no significant differences in OS based on receipt of adjuvant radiotherapy, chemotherapy, or chemoradiotherapy. Conclusion: Salivary ductal carcinoma represents an uncommon and aggressive subset of salivary tumors for which current adjuvant treatments do not have a detectable impact on overall survival.